Marital breakdown in Muslim community in Malaysia - Ismail, Zainab (IDOSI Publications, 2014)
Malaysia has recently witnessed remarkable changes in family life of her population.In the context of divorce, most couples end up their marriage in divorce.The paper aimed at describing the incidence of divorce in Muslim Community in Malaysia.To meet this aim, the article utilizes a content analysis approach using secondary materials which include reports from Population and Housing Census of Malaysia and record files of the Jabatan Kemajuan Islam Malaysia (the Department of Islamic Development Malaysia). The study shows that the divorce rates among Malaysian Muslims aged between 18 and 50 in the country is increased significantly.The data also reveal the highest divorce rates are found in the Federal Territory Kuala Lumpur, followed by Terengganu, Perlis and Kedah.